Promoting mental health in traumatic brain injury using single-session Behavioural Activation and SMS messaging: A randomized controlled trial. Issue 8 (13th September 2020) - Hart, Tessa; Vaccaro, Monica; Collier, George; Chervoneva, Inna; Fann, Jesse R.
ABSTRACT: We compared two treatments for depression and/ or anxiety in chronic moderate to severe traumatic brain injury (TBI) (Clinicaltrials.gov NCT02061553). Fifty-nine participants were randomized 2:1 to a single session of Behavioural Activation followed by 8 weeks of daily SMS (text) messages in the form of implementation intentions supporting individualized goals for increased rewarding/ meaningful activities (INT), or a single (attention control) session focused on the importance of motivation followed by 8 weeks of motivational SMS messages (MOT). Both conditions resulted in modestly improved emotional status. The INT condition led to more exposure to environmental reward and greater productivity. Gains in both conditions were of questionable clinical significance but suggested different mechanisms of action, which should be confirmed by further research. The delivery of frequent text messages proved to be a very feasible means of supporting treatment in this population.